Psychological and spiritual well-being aspects of the quality of life in colostomy patients - Repic, Gordana B; Ivanović, Sunčica; Stanojević, Čedomirka; Trgovčević, Sanja (Vojnosanitetski pregled, 2020)
Background/Aim. Colorectal cancer and its treatment can have a negative impact on the quality of life which has become an important outcome measure for cancer patients. The aim of this work was assessment of psychological and spiritual dimension of the quality of life in colostomy patients, regarding the gender and age. Methods. This is a cross-sectional study conducted at the Abdominal Surgery Polyclinic in the Clinical Canter of Vojvodina among colostomy patients operated between January 2010 and June 2011. The instrument used in this study was Quality of Life Questionnaire for a Patient with an Ostomy (QOL-O). Results. Majority of respondents were male (M:F = 50.7% : 49.3%). The age ranged between 36–86 years. Respondents did not report difficulties in adjustment to stoma, but their great difficulty was to look at it and the sense of depression and anxiety. The care of stoma was worse perceived by younger respondents (p = 0.014). Respondents were mostly satisfied with their memorizing ability and having the sense of control. The lowest score was found in sensing satisfaction or enjoyment in life. The age had a significant impact on positive aspects of psychological well-being (p < 0.05). Higher scores were found among younger age groups. The mean score of spiritual well-being (6.47 ± 3.01) was lower than the mean score of psychological well-being (7.76 ± 2.35). There were no statistically significant differences regarding gender (t = -0.738, df = 65, p = 0.463) or age (F = 1.307, p = 0.280). Conclusion. Psychological and spiritual well-being in colostomy patients appeared to be at satisfactory level, but it is necessary to provide tailor made support in order to prevent and resolve negative responses to stoma.